Karl Polanyi in Vienna - Dale, Gareth (Historical Materialism, 2014)
In this article I discuss Polanyi's intellectual formation in early twentieth-century Budapest and in 1920s Vienna, focusing in particular upon his relationship to Guild Socialist and Marxist theory and to Austrian Social Democracy. It was a period in which Marxism was evolving rapidly, and Polanyi was too. In his twenties, he reacted forcefully against what he saw as the evolutionary and deterministic traits of Marxist philosophy. In his thirties, his relationship to Marxism underwent a 'double movement': his long-held doubts about Marxism crystallised into an forceful critique, swiftly followed by a sympathetic dialogue with the ideas and politics of Austro-Marxism, the 'Rousseauian' commitments of which were not unlike his own. I examine Polanyi's relationship with Marxism in each of these phases, and explore the affinities between Guild Socialism and Austro-Marxism. The final section introduces the distinctly un-Polanyian analysis of Austrian Social Democracy offered by Polanyi's wife, Ilona Duczynska.
Keywords: 20th century; Austria; Austro; Austro-Marxist school; DUCZYNSKA, Ilona; Hungary; Marxism; Marxist philosophy; ROUSSEAU, Jean-Jacques; Vienna (Austria); biography; communism; determinism; functional theory; guild socialism; history; intellectual life; social democracy

The Double Movement of Immovable Property Rights in Papua New Guinea - Filer, Colin (Journal of Pacific History, 2014)
Papua New Guinea (PNG) is one of many countries around the world where the relationship between customary land tenure and economic development has been hotly debated for a long time. A commonplace of the debate in PNG is that 97% of the nation's land is held under customary tenure, while only 3% has been alienated, and these proportions have not changed since the country became independent in 1975. This paper shows that the boundary between customary and alienated forms of land or immovable property was already showing signs of instability in the late colonial period, and this instability has been greatly magnified in the post-colonial period. The areas of land subject to some form of partial alienation have increased along with the ways and means by which immovable property has been ‘mobilised’, while a variety of customary claims to previously alienated areas have grown stronger over the same period. Although Karl Polanyi's idea of a ‘double movement’ can throw some light on this phenomenon, the PNG case also reveals a new side to the application of this concept.
Keywords: Papua New Guinea; agriculture; forestry; forests and forestry; land tenure; mineral industries; mining; politics and government; property rights